Effectiveness of photothermal therapy using various noble-metal photothermal agents - Kim, Donghyuk; Kim, Hyunjung (International Journal of Thermal Sciences, 2024)
Nanosized materials are used in various industries, depending on their production form. In the medical field, nanosized particles are used for treatment. Among various treatment techniques, photothermal therapy (PTT) uses nanoparticles as photothermal agents (PTAs). In this study, the effectiveness of PTT using noble-metal PTAs with various materials and radii was analyzed using numerical analysis. For squamous cell carcinoma within the skin layer, the thermal behavior of the medium was analyzed when PTT was performed by varying the material and radius of the noble-metal PTAs, the volume fraction of the injected PTAs, and the intensity of the irradiating laser. The optical properties of the PTAs and tissue and the temperature distribution in the tissue under laser irradiation were calculated using the discrete dipole approximation method, the Dombrovsky relation, and the Pennes bioheat equation. In addition, an apoptotic variable was derived based on the calculated temperature distribution, and the optimal treatment conditions for each PTAs material were analyzed. The results of the study showed that the maximum therapeutic effect was achieved at a volume fraction of 10−6 and laser intensity of 0.16 W when all PTAs were used, and the difference in therapeutic effect was insignificant with respect to the radius of the nanoparticles. Accordingly, an accurate PTT can be performed using each PTAs material if the proposed treatment conditions are applied.
Keywords: Medical fields; Nanosized materials; Nanosized particle; Noble metal nanoparticles; Photo-thermal; Photothermal agent; Photothermal therapy; Therapeutic effects; Thermal damage; Treatment conditions; Apoptosis; Noble-metal nanoparticles; Photothermal agents; Photothermal therapy; Thermal damage